Motivasi Belajar Memoderasi Pengaruh Kompetensi Dosen Terhadap Tingkat Pemahaman Akuntansi Mahasiswa IAIN Metro - Lella Anita; Northa Idaman (Universitas Muhammadiyah Metro, 2022)
v>The purpose of this study is to test and provide proof of empirically the influence oflecturers competencies to the level of understanding of accounting with the learningmotivation as a moderating variable. This research uses descriptive quantitativemethod. The population of this research is the students of islamic accountingFaculty of Economics and Business Islam IAIN Metro which amounts to 110people. Sampling using purposive sampling method. The analysis technique used isStructural Equation Model (SEM) by using an application program Partial LeastSquare (PLS) version 3.0.m. The results of this study show that (1) the Competenceof the lecturers have a significant effect on the level of understanding of accounting.This supports the hypothesis. (2) Motivation to learn is able to moderate theinfluence of lecturers ' competencies to the level of understanding of accounting.This supports the hypothesis.